RUSSIAN-ARAB COOPERATION BEFORE AND AFTER THE "ARAB SPRING" - M. A. Sapronova (Vestnik MGIMO-Universiteta)
The article considers the main stages of the Russian- Arab economic cooperation since the beginning of the 1990s up to the present time and changing the «Middle Eastern vector» of Russian foreign policy. Analyzes the problems faced by Russia in the development of foreign policy doctrine in the region of the Arab East, becoming the successor of the Soviet Union; difficulty in building bilateral relations with Iraq, Syria, Libya, and Russia's role as a co-sponsor of the Middle East settlement. Next is considered the foreign policy in 2000 and the return of Russia to the «Greater Middle East», analyzes the problems impeding effective Russian- Arab cooperation. Special attention is paid to the strengthening of bilateral relations with the countries of the Arabian Peninsula, the implementation of joint projects in various fields and to establish a constructive dialogue with the new government of Iraq and the establishment of a sound legal framework of mutual relations. Another important direction of Russian foreign policy in the 2000s, becoming the establishment of relations with the Organization of the Islamic Conference. Simultaneously being established permanent contacts with groups «Hamas» and «Hezbollah». In the last part of the article explores the specificity of modern political, trade and economic cooperation after the events of the «Arab Spring» of 2011. Particular attention is paid to the position of Russia in relation to processes taking place in Tunisia, Egypt, Libya, Syria. The crisis in Syria has demonstrated a fundamentally different approaches to its solution by Russia and the West. Ultimately, the firm position of Russia on the Syrian issue secured her role as an important political player in the Middle East. In general, regional transformation in 2011, despite their negative consequences for the Russian-Arab economic cooperation and opened new opportunities to promote the Russian Federation for Arab markets.